PREVALENCE OF MALNUTRITION IN CHILDREN UNDER 2 YEARS AND ITS ASSOCIATION WITH SUBOPTIMAL BREASTFEEDING PRACTICES - Dr Tufail Ahmed Soomro; Dr Afsheen Batool Raza; Dr Poonam Kataria; Dr Waseem Pasha; Dr Nayyar Ahmad; Dr Mian Sarfraz Gul (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: Malnutrition in children under two years remains a significant public health issue in developing countries, including Pakistan. Breastfeeding practices play a pivotal role in determining a child’s nutritional status during this critical growth period.Objective: To assess the prevalence of malnutrition among children under two years of age and examine its association with sub-optimal breastfeeding practices in a hospital-based population in Pakistan.Materials and Method: A descriptive cross-sectional study was conducted at multiple center including Department of Paediatrics, Shahida Islam Teaching Hospital Lodhran, Pakistan and Rehman Medical Institute Hayatabad Peshawar, Pakistan in the duration from January 2024 to June 2024. Data were collected from 250 children using structured questionnaires and anthropometric measurements. WHO growth standards were used to assess nutritional status, and SPSS version 26 was used for statistical analysis.Results: Stunting (44.8%), underweight (38%), and wasting (29.2%) were prevalent. Suboptimal breastfeeding practices, including delayed initiation and non-exclusive breastfeeding, showed a significant association (p